AB0695 Dose tapering of infiximab in patients with spondyloarthritis. (15th June 2017) - Correyero, M; Nieto, JC; González, CM; Lόpez, A; González, R; Saenz, C; García-Montoya, L; Longo, FJL; Monteagudo, I
Abstract : Background: Infliximab have proven to be effective in spondyloarthritis. Previous studies suggest that patients in clinical remission may benefit from dose reduction or pharmacological tapering without relapse. Objectives: To study the evolution of clinical activity and physical function in patients with spondyloarthritis, ankylosing spondylitis (AS) and psoriatic arthritis (PsA) under Infliximab (IFX) tapering strategy. Methods: This is a prospective single-centre observational study of patients diagnosed with AS and PsA treated with IFX (5 mg/kg/infusion) between January 1, 2012 and December 31, 2015. We included patients who achieved clinical remission or low activity index (expressed with BASDAI and BASFI) and decided to lower the dose of 5 to 4 mg/kg/infusion, maintaining the periodicity of the treatment in each patient. Demographic data (age, gender, time with IFX) daily activities, physical activity (BASDAI and BASFI) and laboratory data (ESR and CPR) were collected at the baseline visit prior to tapering, at the next infusion following dose reduction and the last infusion (between November 1st 2014 and December 31st, 2016). Results: We included 18 patients (16 men) on IFX treatment with EA (16) or axial APs (2). The medians of age and time of evolution were 50.79 years (41.8–55.1) and 9.5 years (7.2–11.5), respectively. Table 1 shows the clinical and laboratory data obtained at the baseline visit, the next infusion and the last infusion. Fourteen patients (87.9%) continued with the dose of 4 mg/kg/infusion and are maintained in clinical remission. Four patients returned to the dose of 5 mg/kg/infusion due to loss of efficacy at dose reduction, with a mean follow-up of 17.6 months (17.0–19.1). Clinical remission was again achieved in the 4 patients, although one of them changed biological therapy due to loss of efficacy of IFX after 3 infusions with 5 mg/kg/infusion. Conclusions: In our patients with spondyloarthritis dose reduction of IFX was well tolerated and safe, maintaining the clinical response measured by BASDAI and BASFI. In 3 out of 4 patients who worsened upon dose reduction, the 5 mg/kg/infusion dose recovered clinical remission. References: Janta I et al. Clin Rheumatol. 2015;34: 935–42. Baraliakos X et al. RMD Open. 2016;2: e000272. Disclosure of Interest: None declared